"Hybridised" financial control in the Victorian construction industry: George Gilbert Scott's rebuilding of Glasgow University, 1864–1872. (May 2015) - McKinstry, Sam; Ding, Ying Yong
This article examines the financial control of Scotland's largest building construction project of the 1860s and 1870s, the relocation of Glasgow University at Gilmorehill. In discussing the respective roles of the architect, the "measurer" (quantity surveyor), the client, the clerk of works and the various contractors engaged to carry out the construction work, particular attention is given to the detailed management processes and involvements which contributed to the project's financial control and, ultimately, its success. The study relates this system of control to the literature on "hybridised" accounting and also to that concerning management accounting change within institutions. It also comments on the activities and professional status of the "measurer", whose work was central to the project's financial management system.